Mining and Metallurgy Industry in the History of Economic Development of New Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article is devoted to the development of the mining industry, the natural location and socio-economic history of one of the most important industrial complexes in Uzbekistan. The expansion of the mining industry complex, the commissioning of new capacities and the reconstruction of the existing enterprises, the industrial and technical base of the complex and its importance in the industry of the republic are given brief information.